Nitrogen Reserve Pools in Two Miscanthus × giganteus Genotypes under Contrasting N Managements - Dierking, Ryan M.; Allen, Damian J.; Cunningham, Suzanne M.; Brouder, Sylvie M.; Volenec, Jeffrey J. (Frontiers in Plant Science, 2017)
Nitrogen (N) reserves in vegetative tissues contribute N to regrowth of Miscanthus × giganteus shoots in spring, but our understanding of how N fertilization and plant genotype affect this process is incomplete. Our specific objectives were to: 1) determine how N fertilizer management impacts accumulation of dry matter (DM) and N among aboveground and belowground tissues and organs; 2) understand how changes in N management and tissue N concentration influence seasonal fluctuations in concentrations of buffer-soluble proteins and amino acids in putative storage organs including rhizomes and roots; and 3) characterize genotypic variability and genotype x N interactions for N reserve accumulation and use among Miscanthus × giganteus genotypes. Established plots of the IL Clone and Nagara-sib population were fertilized with 0-0, 0-150, 75-75, 150-0, and 150-150 kg N ha-1 where the first numeral denotes the N rate applied in 2011 (Year 1) and the second number denotes the N rate applied in 2012 (Year 2). Rhizomes, roots, stembases, and shoots were sampled at six-week intervals between March and August and then in November at dormancy. Concentrations of N, soluble protein and amino-N increased in all tissues with fertilizer N application. With the exception of rhizome amino-N, concentrations of these N pools in roots and rhizomes declined as plants resumed growth in spring and increased sharply between August and November as growth slowed. Losses in shoot and stembase N mass between August and November were similar to total N accumulation in roots and rhizomes during this interval. Compared to the unfertilized control, specific N managements enhanced growth of above- and belowground tissues. The IL Clone generally had greater biomass yield of all organs than the Nagara-sib; the exception being shoot biomass in November when extensive leaf senescence reduce yield of the IL Clone. High biomass yields were obtained with 75 kg N ha-1 applied annually rather than semi-annual N applications of 150 kg N -1 ha that depended on N recycling from roots/rhizomes as a supplemental N source.